2019
DOI: 10.22146/jcef.43760
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Lava Sand Filtration for Decentralized Produced Water Treatment System in Old Oil Well Wonocolo

Abstract: The Cepu Block Oil Field has been traditionally extracted since 2008 by the local community in Wonocolo. The oil well-produced gas and fluids consisted of crude oil and produced water. This oil production activity discharges high amounts of produced water. The fluids have been settled down in the sedimentation tank to gain the crude oil optimally. The remaining fluid called produced water has been discharged to the surface towards the river without any further treatment.  This activity led to the deterioration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Many previous studies have stated that the existence of traditional oil mines in Wonocolo caused the quality of river water in Wonocolo to be polluted (Hedar, 2018;Marwoto, 2012;Sari & Trihadiningrum, 2018;Yogafanny, et al, 2019), based on physicochemical parameters of river water, before the Covid pandemic -19 in progress. However, the result of a research on river water quality in Wonocolo, during the Covid-19 pandemic, showed a different result from those of previous studies; namely, there was an increase in river quality during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have stated that the existence of traditional oil mines in Wonocolo caused the quality of river water in Wonocolo to be polluted (Hedar, 2018;Marwoto, 2012;Sari & Trihadiningrum, 2018;Yogafanny, et al, 2019), based on physicochemical parameters of river water, before the Covid pandemic -19 in progress. However, the result of a research on river water quality in Wonocolo, during the Covid-19 pandemic, showed a different result from those of previous studies; namely, there was an increase in river quality during the pandemic.…”
Section: Introductionmentioning
confidence: 99%